2005
DOI: 10.1086/430601
|View full text |Cite
|
Sign up to set email alerts
|

Three Broad Modalities in the Natural History of Vertically Acquired Hepatitis C Virus Infection

Abstract: We confirm the low prevalence of HCV-related clinical signs and symptoms among vertically infected children in the first 10-15 years of life. Approximately 20% of children appear to clear the infection, 50% have evidence of chronic asymptomatic infection, and 30% have evidence of chronic active infection. Although viremia and abnormal ALT levels were associated with hepatomegaly, further investigation is necessary before these markers can be used in the clinical management of HCV infection in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(55 citation statements)
references
References 18 publications
1
49
0
5
Order By: Relevance
“…We excluded data points in which HIV status among the sample of mothers was mixed (combined groups of HIV-positive and HIV-negative mothers) or unknown (women were not tested for HIV or HIV status was not reported by the study), as well as studies with sample sizes of <11 children assessed for infection at follow-up. Clearance of viremia among children with transient RNA positivity occurs at the median age of 15 months [29, 30], whereas 95% of children diagnosed as uninfected lose maternal antibodies by 12 months of age [31]. In addition to circulating HCV viremia, the presence of HCV antibodies at ≥18 months of age has been used as a surrogate measure of infection [32].…”
Section: Methodsmentioning
confidence: 99%
“…We excluded data points in which HIV status among the sample of mothers was mixed (combined groups of HIV-positive and HIV-negative mothers) or unknown (women were not tested for HIV or HIV status was not reported by the study), as well as studies with sample sizes of <11 children assessed for infection at follow-up. Clearance of viremia among children with transient RNA positivity occurs at the median age of 15 months [29, 30], whereas 95% of children diagnosed as uninfected lose maternal antibodies by 12 months of age [31]. In addition to circulating HCV viremia, the presence of HCV antibodies at ≥18 months of age has been used as a surrogate measure of infection [32].…”
Section: Methodsmentioning
confidence: 99%
“…Children with chronic hepatitis C infection are most often asymptomatic, although mild nonspecific symptoms can occur. In one study of children who acquired the infection in the perinatal period, approximately 10% were found to have hepatomegaly over the first 4 years of life; however, the same study confirmed the low overall prevalence of HCV‐related clinical signs and symptoms during the first 15 years of life 47. The majority of HCV‐infected children will have intermittent or persistent liver enzyme elevations.…”
Section: Clinical Featuresmentioning
confidence: 97%
“…4247 Spontaneous viral clearance in perinatal HCV infection was more common with HCV genotype 3 and usually occurred by age 3 years. 46,48 Spontaneous viral clearance also has been associated with the presence of CC interleukin-28 (IL28B) host genotype in perinatally HCV-infected infants. 49 …”
Section: Hepatitis C Virus (Last Updated November 6 2013; Last Reviementioning
confidence: 99%
“…45,5456 In a large European cohort of HCV-infected children, about 20% of children had apparent clearance of HCV viremia; 50% had chronic asymptomatic infection, characterized by intermittent viremia, rare hepatomegaly, and usually normal liver transaminase levels; and 30% had chronic active infection with persistent viremia and abnormal transaminase levels. 46 …”
Section: Hepatitis C Virus (Last Updated November 6 2013; Last Reviementioning
confidence: 99%